18F-FDG PET/CT features of pulmonary sclerosing hemangioma. (February 2013) - Lee, Eugene; Park, Chang Min; Kang, Keon Wook; Goo, Jin Mo; Kim, Min A; Paeng, Jin Chul; Lee, Hyun Ju; Park, Heae Surng; Chung, Doo Hyun
Background: Pulmonary sclerosing hemangioma (PSH) has been reported to show increased FDG uptake and be potential false-positives on 18F-FDG PET/CT examination. However, it is still unclear whether the previously-reported high FDG uptake is a universal characteristic of PSH, and furthermore, there have been no investigations on what kind of radiologic or histologic features may have been related with its FDG uptake values. Purpose: To investigate the 18F-FDG PET/CT features of pulmonary sclerosing hemangiomas (PSHs), and to evaluate the relating factors with their FDG uptake values. Material and Methods: We identified 10 PSHs in eight patients who had a pathologic diagnosis and available antecedent 18F-FDG PET/CT images. 18F-FDG PET/CT images were investigated both qualitatively and quantitatively, along with their histopathologic features. Correlation between 18F-FDG PET features and radiologic as well as histopathologic features were also evaluated. Results: Mean diameter of the 10 PSHs in our study was 16.9 mm ± 6.26 (range 5-25 mm). Four tumors showed intense uptake, and four tumors showed moderate uptake on 18F-FDG PET/CT scans. In the remaining two tumors, there were no significant FDG uptakes. The SUVmax of tumors ranged from 0.60-4.7 (median 2.30; 2.51 ± 1.42), and was significantly correlated with the tumor size (r = 0.754, P = 0.012) and three out of four tumors ≥2 cm (75%) showed intense FDG uptake and their SUVmax values were greater than 2.5. Immunohistochemical results for GLUT-1, GLUT-4, and Ki-67 and other pathologic features were not correlated with the tumors' FDG uptake. Conclusion: The majority of PSHs show increased FDG uptakes, and their SUVmax values are significantly correlated with their tumor size. PSH ≥2 cm can frequently be falsely interpreted as malignancy in FDG-PET/CT. Further studies with large study population are warranted to confirm our observations.